Measuring human salivary amylase copy number variation - Dhar, Sugandha (2010)
Copy number variations represent large scale genomic alterations varying from 1kb to 3Mb and are proposed as a driving force for genome evolution and variation. One such locus exhibiting copy number variation and genome evolution is salivary amylase, which is responsible for the digestion of starch in the human parotid glands. It was reported that since human salivary amylase gene (AMY1) copy numbers are correlated positively with protein levels, and also due to the correlation of high gene copy numbers with a starch rich diet, AMY1 had undergone adaptive evolution. Moreover there was recent evidence for gain of copy number in the human lineage concordant with the dietary shift which occurred during Neolithic times. The main focus of this study was the development of multiplex Paralogue Ratio Test (PRT) systems for measuring human amylase copy number. Despite having considerable identity between salivary amylase and pancreatic amylase copies, PRT was designed due to the exclusive association of a retroviral element with the salivary amylase gene copies, such that only salivary amylase copies were quantified. As retroviral elements are scattered throughout the genome therefore eliciting amplification from just test and reference without any contribution from alternative loci was a technical challenge in this project. However, creation of enough mismatches within the primer binding sites ensured that only the test and reference sequences were amplified. Discrimination by means of increasing annealing temperature also aided in exclusive amplification of test and reference sequences. Consequently, two PRTs and 1 microsatellite assay were successfully designed to measure copy number of AMY1 in Japanese and UK DNA samples. 14 copies was the highest copy number seen in the samples from both PRT systems. Reference samples specifying individual classes of copy number exhibited strong relationship with the copy numbers as determined by previous work. Repeat testing and clustering of copy number data points by both the individual systems of measurement ascertained the accuracy and reproducibility of the developed assays.